2021
DOI: 10.3390/ma15010100
|View full text |Cite
|
Sign up to set email alerts
|

Early-Age Mechanical Properties of 3D-Printed Mortar with Spent Garnet

Abstract: This study determines the effect of spent garnet as a replacement for natural sand in 3D-printed mortar at early ages. Five mixes with different spent garnet amounts were prepared (0%, 25%, 50%, 75% and 100% by volume). The ratio of binder to aggregate remained unchanged. In all mixes the water/binder ratio was assumed as a constant value of 0.375. Tests were performed to confirm the printability of the mix (a path quality test using a gantry robot with an extruder). Determinations of key buildability properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Firstly, it should be noted that the green strength obtained for materials modified with the fine recycled aggregate (fRA) ranges between 5.27 kPa and 11.09 kPa after 30 min and between 6.26 kPa and 14.73 kPa for specimens tested for 60 min. These values are in line with those presented in other studies [ 13 , 15 , 30 , 32 , 50 ]. Chosen research teams that focused on ordinary mixes without recycled aggregate incorporation obtained the following results after 30 min: Casagrande et al [ 32 ] reported values of between 4.30 kPa and 26.04 kPa, Wolfs et al [ 50 ] reported about 10.5 kPa, Panda et al [ 51 ] reported about 10.65 kPa, and Skibicki et al [ 30 ] reported about 9.02 kPa.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Firstly, it should be noted that the green strength obtained for materials modified with the fine recycled aggregate (fRA) ranges between 5.27 kPa and 11.09 kPa after 30 min and between 6.26 kPa and 14.73 kPa for specimens tested for 60 min. These values are in line with those presented in other studies [ 13 , 15 , 30 , 32 , 50 ]. Chosen research teams that focused on ordinary mixes without recycled aggregate incorporation obtained the following results after 30 min: Casagrande et al [ 32 ] reported values of between 4.30 kPa and 26.04 kPa, Wolfs et al [ 50 ] reported about 10.5 kPa, Panda et al [ 51 ] reported about 10.65 kPa, and Skibicki et al [ 30 ] reported about 9.02 kPa.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies dedicated to the incorporation of recycled aggregates present inconclusive results. For example, Ding et al [ 15 ] indicate an increase in green strength after incorporating recycled sand, from 10.68 to 12.23 kPa, while Skibicki et al [ 13 ] prove that the addition of recycled aggregate leads to a decrease in green properties (from about 14 kPa to 3.8 kPa). Based on the presented examples, (i) in both studies, the recycled aggregate was used as a substitution for a natural aggregate, while, in the presented paper, the authors substituted the binder; and (ii) the obtained values in the presented papers [ 13 , 15 ] are comparable to the values obtained in this current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite reducing flowability and extrudability in the fresh state, AMFs improved the hydration reaction speed with increased shape stability and long-term strength [111]. The relation between printability and mechanical performance with size gradation and interlayer distribution was proved by incorporating recycled concrete, desert sand, and river sediment [112] and preserving buildability with up to 50% replacement of sand with spent garnet [113].…”
Section: Biomass-based Casting Process 3dcpmentioning
confidence: 99%